2004
DOI: 10.1021/ja031981t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure Solution, Characterization, and Catalytic Properties of TNU-10:  A High-Silica Zeolite with the STI Topology

Abstract: A high-silica zeolite (Si/Al = 7.1) with the STI framework topology, denoted TNU-10, has been synthesized in the presence of 1,4-bis(N-methylpyrrolidinium)butane and Na(+) cations as structure-directing agents, and its structure in the proton form has been refined against laboratory powder X-ray data in space group Fmmm (a = 13.533(1) A, b = 17.925(2) A, c = 17.651(2) A). The space group symmetry is supported by electron diffraction and energy minimization studies. The as-made and proton form of TNU-10 are ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 29 publications
2
60
1
1
Order By: Relevance
“…For example, reasonably good HRTEM images have been obtained from zeolites, C 60 /trimethylbenzene composite, and MOFs. [32][33][34][35] Using a very low dose of electron beam, some HRTEM images of fragments of MOF-5 nanoplates were obtained as shown in Figures 5e and 5f. Although some structural degradation is visible in the HRTEM images, weak crystalline fringes are observed along the profile and long axis of the nanoplates.…”
Section: Resultsmentioning
confidence: 99%
“…For example, reasonably good HRTEM images have been obtained from zeolites, C 60 /trimethylbenzene composite, and MOFs. [32][33][34][35] Using a very low dose of electron beam, some HRTEM images of fragments of MOF-5 nanoplates were obtained as shown in Figures 5e and 5f. Although some structural degradation is visible in the HRTEM images, weak crystalline fringes are observed along the profile and long axis of the nanoplates.…”
Section: Resultsmentioning
confidence: 99%
“…Zeolite TNU-9 was synthesized according to the procedure described previously [21,22], using 1,4-bis-(N-methylpryrrolidinium)-butane and Na + cations as structure directing agents (SDAs). ITQ-2 was prepared by swelling the MCM-22 precursor with a water solution of hexadecyltrimethylammonium bromide and tetrapropylammonium hydroxide following the method depicted in previous publications [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…This is very encouraging, as ever more complex structures are prepared, and suggests that an inability to grow single crystals should not limit our discovery of their intricate architectures. Both TNU-9 and IM-5 crystallize in the presence of the same organic SDA, bis-N-methylpyrrolidiniumbutane, which has also been shown to favor the crystallization of several other zeolites depending on solution pH, Si/Al ratio, additional cations, and so on [29]. This is a clear indication that the detailed composition of the hydrothermal reaction mixture plays a crucial role in supplying species for the growth of these complex solids.…”
Section: The Current Limits Of Structural Complexity In Zeolitesmentioning
confidence: 89%
“…Zones has investigated the effect of variation of Si/Al and Si/B ratios in the gel as additional parameters in the syntheses with new potential SDAs [26], and Corma (and the Mulhouse and Stockholm groups) found that the inclusion of germanium had a strong structure-directing influence, because of its propensity to favor the formation of D4Rs [11, 27,28] . Furthermore, the addition of inorganic cations and variation of alkalinity (OH − /T) have been shown to have an important influence on the zeolite structure to form [29].…”
Section: Introductionmentioning
confidence: 99%